Theological Education at the Crossroads. (December 2014) - Ladd, Nick
Abstract Theological education and ministerial training must prepare people for a post‐Christendom context. Moving on from the subject‐object dualism of modernity, where ministry is seen as a professional task done to and for others, this article proposes that attending to the subjectivity of others is necessary for the formation of mature community, and for genuine missional engagement. It proposes a contextualised training in which students learn theologically reflective practice from the heart of Christian community.